2014
DOI: 10.4103/0971-9261.136471
|View full text |Cite
|
Sign up to set email alerts
|

Management of complicated ureteroceles: Different modalities of treatment and long-term outcome

Abstract: The presentation and management of ureterocele has been rarely reported from India and is limited to an odd case report. They can be detected antenatally, may have incidental diagnosis or present with consequences of obstructive uropathy. They always present with secondary complications in adulthood, if the diagnosis and treatment is missed in early years of life. The natural history may be particularly disastrous in cases of bilateral obstructing ureterocele. The complications secondary to obstructive uretero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Ureterocele is reported to affect one in 4000 individuals. 5 Few cases of ureterocele have been documented in our country with none complicated with renal failure. It is bilateral in 10% of cases with female preponderance.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ureterocele is reported to affect one in 4000 individuals. 5 Few cases of ureterocele have been documented in our country with none complicated with renal failure. It is bilateral in 10% of cases with female preponderance.…”
Section: Discussionmentioning
confidence: 95%
“…Such individuals will require renal replacement therapy for survival. In their case series, Chowdhary et al 5 reported various complications of ureterocele including development of end stage renal failure. In a review of 305 children in a tertiary hospital, Hari et al 7 documented a high proportion of renal failure due to obstructive uropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Otherwise, many patients can be managed conservatively. 15,16 Surgery can be performed endoscopically or through the open approach with excision of the ureterocele and upper pole partial nephrectomy or common sheath reimplantation. 17 Considering its success for intravesical ureteroceles, endoscopic intervention has become the initial choice for nearly two decades.…”
Section: Discussionmentioning
confidence: 99%
“…The ureterocele is an abnormal cystic dilatation of distal intramural end of the ureter into the bladder [1]. The most common accepted theory for its pathogenesis is the incomplete dissolution of Chwalla's membrane [2].…”
Section: Discussionmentioning
confidence: 99%